Exploring the Accounting Treatment of Exploration and Evaluation Activities in the Extraction Industry in South Africa and Australia - Van der Walt, Christa; Dlamini, Banele; Schutte, Danie P (International Journal of Economics and Financial Issues, 2023)
The study examines the accounting treatment of exploration and evaluation assets in the extraction industry in South Africa and Australia. This study adopted a qualitative research approach and purposive sampling techniques. Data was collected from 60 entities in the extraction industry that are listed on the Johannesburg Stock Exchange (JSE) and the Australian Securities Exchange (ASX). The study found that South African entities classify exploration and evaluation assets as tangible or intangible assets using International Financial Reporting Standard (IFRS) 6. The study also observed that Australian entities classify exploration and evaluation assets as a separate class of assets using the Australian Accounting Standard Board (AASB) 6. South African entities depreciated or amortized exploration and evaluation assets, while Australian entities did not. The study concluded that even though there is high adoption of IFRS 6 or AASB 6, comparability is compromised in the extraction industry. The study recommended that IFRS 6 not offer a choice between IAS 16 or IAS 38 for the classification of exploration and evaluation assets to improve comparability and aid effective decision-making.